Optical coherence tomography assessment of in-stent restenosis after percutaneous coronary intervention with two-stent technique in unprotected left main. (15th September 2016) - Fujino, Yusuke; Attizzani, Guilherme F.; Tahara, Satoko; Naganuma, Toru; Takagi, Kensuke; Yabushita, Hiroto; Wang, Wei; Warisawa, Takayuki; Watanabe, Yusuke; Mitomo, Satoru; Sato, Tomohiko; Kurita, Naoyuki; et al.
Abstract: Background: Optical coherence tomography (OCT) has contributed to a better understanding of in-stent restenosis (ISR); however, studies evaluating ISR pattern after two-stent technique in unprotected left main (ULM) are lacking. We aim to evaluate the ISR pattern of proximal LAD and LCX after two-stent technique in ULM. Methods: We performed OCT in 26 patients with isolated or combined ISR (identified by angiography as > 50%) after two stent implantation in the proximal LCX and LAD. Finally, 13 LAD and 22 LCX ISR lesions underwent OCT assessments. OCT analyses were undertaken in the proximal segments of the LAD and LCX. In addition, we compared OCT findings in the flow divider (FD) and lateral wall (LW). Results: In both the LAD and LCX, the distance from the ostium to the minimum lumen area (MLA; LAD, 2.00 mm [1.00, 3.00]; LCX, 1.00 mm [0.00, 1.80] distal to ostium) was short. Uncovered struts were more common on the FD side compared with the LW in the LAD (6.25% [0.00, 20.00] vs 0.00% [0.00, 0.00], respectively, p = 0.016) and LCX (11.32% [0.00, 19.44] vs 0.00% [0.00, 4.55], respectively, p < 0.001). Conversely, neointimal hyperplasia (NIH) was significantly thicker on the FD side compared with the LW in the LCX (0.31 mm [0.19, 0.47] vs 0.15 mm [0.09, 0.31], p < 0.001). Conclusions: While uncovered struts were more commonly found on the FD side of both arteries, NIH was significantly thicker on the FD side compared with the LW in the LCX. These unique findings might indicate inferior outcomes after two-stent techniques in ULM bifurcation lesions.